Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376241
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Enhancing Access and Efficacy of Peer Sponsorship in Substance Use Disorder Recovery

Abstract: Substance use disorders (SUDs) are characterized by an inability to decrease a substance use (e.g., alcohol or opioids) despite negative repercussions. SUDs are clinically diagnosable, hazardous, and considered a public health issue. Sponsorship, a specialized type of peer mentorship, is vital in the recovery process and originates from 12-step fellowship programs such as Alcoholics Anonymous (AA) and Narcotics Anonymous (NA). To investigate sponsorship relationship practices and to identify design opportuniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…For example (as described in our results section 4.3), P11 and P28 both experienced a lack of support from their online networks after posting about difcult negative experiences on social media, which discouraged them from posting similar content in the future. Instead, research has shown that people turn to small groups of close connections or private channels [37,41,80], anonymous online sharing [4,46], and multiple or separate online identities [20,35,79] to achieve online sharing that feels authentic to them. In what follows, we describe future directions for design and research that can help to resolve some of the tensions the online authenticity paradox highlights.…”
Section: Discussionmentioning
confidence: 99%
“…For example (as described in our results section 4.3), P11 and P28 both experienced a lack of support from their online networks after posting about difcult negative experiences on social media, which discouraged them from posting similar content in the future. Instead, research has shown that people turn to small groups of close connections or private channels [37,41,80], anonymous online sharing [4,46], and multiple or separate online identities [20,35,79] to achieve online sharing that feels authentic to them. In what follows, we describe future directions for design and research that can help to resolve some of the tensions the online authenticity paradox highlights.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Savings and overdraft facilities are found to be insignificant at p = 0.05, which means they are relatively insignificant in comparison with other financial factors. These findings are supported by Heyer, Schmitt, Dombrowski, and Yarosh (2020), who emphasized that growth in most businesses is due to access to credit facilities, grants, and sponsorship. Heyer et al (2020) and Omondi-Ochieng (2020) report that donation and sponsorship account for 87.5% of enterprises' financial performance.…”
Section: Resultsmentioning
confidence: 59%
“…Nicholson et al's approach in [58] provides a conceptual framework for training community peers to act as 'guardians' to disseminate preventative strategies to their community to increase cyber resilience. Heyer et al have also recently highlighted strategies for social computing tools to support dyadic mentorship for recovery from alcohol or drug dependency [38]. However, prior research has yet to investigate how technology might support and expand safe interventions for supporting the desistance of abusive behaviours towards others, despite there being calls to do so [30,66].…”
Section: Peer Support Technologies For Reducing Harmmentioning
confidence: 99%
“…To mitigate the challenges for online support groups, some scholars have explored a hybrid-approach to better understand how technology can leverage existing face-to-face peer support networks and social structures [20,38,59]. In the community-driven approach of Circles of Support and Accountability (CoSA), a circle of trained volunteers connected via a digital network work with sex offenders to minimise alienation and support reintegration after incarceration with the aim of preventing sexual reoffending in their community [84].…”
Section: Peer Support Technologies For Reducing Harmmentioning
confidence: 99%
See 1 more Smart Citation